PAS: Enable Partial Consensus in the Blockchain - Xu, Zihuan; Han, Siyuan; Chen, Lei (Database Systems for Advanced Applications, 2021)
Permissioned Blockchain enables distributed collaboration among organizations that may not trust each other. However, existing systems cannot efficiently support the ordering and execution of transactions in different workflows parallelly, which seriously affects system scalability and performances in terms of throughput and latency. In this paper, we present a partial consensus mechanism named PAS to achieve fault tolerance and parallelism of transaction processing. In PAS, transactions in different workflows only need to be confirmed by the involved subset of nodes, which significantly enhances the system performance and scalability. Specifically, we introduce a novel data structure, called the hierarchical consensus tree (HCT). It is maintained in each node and used to coordinate the consensus process. HCT guarantees that the consistency reached in different sets of nodes is eventually agreed by all nodes without conflicts and rollbacks. Since there are many valid HCTs with different system improvements, we introduce an optimization problem, named OHCT, to obtain an HCT with respect to the optimal enhancement. We prove OHCT is NP-hard and propose a general framework with efficient algorithms to address it. Finally, we implement PAS on PBFT-based Hyperledger fabric and conduct extensive experiments to show the performance and scalability of PAS.